Memory-Efficient Hardware Performance Counters with Approximate-Counting Algorithms - Xu, Jingyi; Kim, Sehoon; Nikolic, Borivoje; Shao, Yakun Sophia (2021 IEEE International Symposium on Performance Analysis of Systems and Software (ISPASS), 2021)
Hardware performance counters are special registers on processors that track the hardware activities. While the performance counter data are useful for many applications, there are challenges in efficiently collecting many event statistics simultaneously, due to the limited number of performance counters on chip. We propose an efficient hardware performance counter design that uses approximate-counting algorithms to improve the number of events tracked on-chip without incurring significant memory overhead. These counters are more memory efficient because they increment counts according to a dynamic probability and approximate the exact counts. Compared with multiplexed hardware performance counters, our approximate hardware counters have a statistically provable memory-accuracy trade-off and are entirely managed in hardware.